Backend Development of a Microservice-Based Website Application for Public Issue Reporting: Case Studyn in People Representative Council - Isnaeni, Rizqullah Maziyah; Utama, Nur Ichsan; Suakanto, Sinung (Journal La Multiapp, 2024)
This research introduces a web application aimed at advancing public issue reporting, promoting civic engagement, and expediting government responses. In collaboration with DPRD Jawa Barat, the research leverages Scrum methodology, social network features, and a microservice architecture to create an efficient communication platform between citizens and governmental bodies. The backend of the application, developed using the Go programming language, adopts a microservice architecture to enhance scalability and maintainability. The Scrum methodology facilitates an agile development process, ensuring adaptability to changing requirements and fostering continuous improvement throughout the project lifecycle. Additionally, the study explores the incorporation of social network features to encourage public engagement within the application. This integration allows citizens to connect, share, and discuss public issues, further enhancing the collaborative nature of the reporting platform. To ensure the seamless functionality of the microservices, API testing is employed, validating the reliability and consistency of the application's interfaces. Stress testing is also conducted to assess scalability and performance capabilities, identifying potential optimizations for the system's responsiveness under varying levels of load. In conclusion, this research presents an innovative solution for public issue reporting that combines microservice architecture, Scrum methodology, and social network features. The application's integration of these elements aims to not only streamline citizen-government communication but also create a dynamic platform that encourages active public involvement and collaboration.